The evolutionarily diverged single-stranded DNA-binding proteins SSB1/SSB2 differentially affect the replication, recombination and mutation of organellar genomes in Arabidopsis thaliana - Weidong Zhu; Jie Qian; Yingke Hou; Luke R. Tembrock; Liyun Nie; Yi-Feng Hsu; Yong Xiang; Yi Zou; Zhiqiang Wu (Plant Diversity)
Single-stranded DNA-binding proteins (SSBs) play essential roles in the replication, recombination and repair processes of organellar DNA molecules. In Arabidopsis thaliana, SSBs are encoded by a small family of two genes (SSB1 and SSB2). However, the functional divergence of these two SSB copies in plants remains largely unknown, and detailed studies regarding their roles in the replication and recombination of organellar genomes are still incomplete. In this study, phylogenetic, gene structure and protein motif analyses all suggested that SSB1 and SSB2 probably diverged during the early evolution of seed plants. Based on accurate long-read sequencing results, ssb1 and ssb2 mutants had decreased copy numbers for both mitochondrial DNA (mtDNA) and plastid DNA (ptDNA), accompanied by a slight increase in structural rearrangements mediated by intermediate-sized repeats in mt genome and small-scale variants in both genomes. Our findings provide an important foundation for further investigating the effects of DNA dosage in the regulation of mutation frequencies in plant organellar genomes.